The Intergenerational Transmission of Financial Stress and Relationship Outcomes. Issue 4 (18th May 2016) - Hubler, Daniel S.; Burr, Brandon K.; Gardner, Brandt C.; Larzelere, Robert E.; Busby, Dean M.
Abstract : Numerous studies have focused on the intergenerational transmission of poverty, financial stress, and family functioning. Other research has shown how financial stressors can predict various family processes, including parent–child interactions, family conflict, and couple communication, and relationship outcomes, including marital stability and satisfaction. This study shows continued evidence that financial stress from the male and female partner's family of origin may predict marital dissatisfaction using dyadic data techniques. Also, an exploration of indirect paths also found that the presence of current financial stress partially mediates these associations.